1987
DOI: 10.1139/b87-313
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of chromosome numbers in the genus Brachiaria (Poaceae: Paniceae) in relation to morphology and taxonomy

Abstract: Determinations of chromosome number and morphological studies of 260 populations, belonging to 32 taxa, of the genus Brachiaria from the Indian subcontinent reveal that all sexually reproducing taxa have no chromosome races. Six agamic taxa, viz., B. brizantha var. brizantha (n = 27), B. brizantha var. ciliata (n = 18), B. decumbens (n = 18), B. hybrida (n = 27), B. mutica (n = 18), and B. setigera var. albistyla (n = 14), have consistently shown uniformity in chromosome numbers, based on x = 7, 8, and 9. Brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 25 publications
3
38
1
Order By: Relevance
“…The same basic chromosome number (x = 9) was recorded for this species by other authors (see Valle and Pagliarini, 2009). Diploidy (2n = 2x = 18) was reported in only a few accessions (Basappa et al, 1987;Mendes-Bonato et al, 2002), but tetraploids always prevail (see Valle and Pagliarini, 2009). In attempt to aid the Brachiaria breeding program underway at Embrapa Beef Cattle and to determine the ploidy level of the accessions of different species to initiate an interspecific hybridization program, DNA content was measured by flow cytometry (Penteado et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The same basic chromosome number (x = 9) was recorded for this species by other authors (see Valle and Pagliarini, 2009). Diploidy (2n = 2x = 18) was reported in only a few accessions (Basappa et al, 1987;Mendes-Bonato et al, 2002), but tetraploids always prevail (see Valle and Pagliarini, 2009). In attempt to aid the Brachiaria breeding program underway at Embrapa Beef Cattle and to determine the ploidy level of the accessions of different species to initiate an interspecific hybridization program, DNA content was measured by flow cytometry (Penteado et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The data on the meiotic behavior of H003 and H030 ascertained that they are heptaploids derived from x = 6. Two basic chromosome numbers, x = 7 and x = 9, have been reported for the genus Brachiaria, with a large prevalence of x = 9 (Basappa et al, 1987;Honfi et al, 1990;Valle and Savidan, 1996;Bernini and Marin-Morales, 2001;Utsunomiya et al, 2005;Mendes-Bonato et al, 2002. However, recently, a new basic chromosome number, x = 6, was determined for several accessions in the germplasm collection of B. dictyoneura at Embrapa (Risso-Pascotto et al, 2006c), a species belonging to the same taxonomic group and closely related to B. humidicola, according to Renvoize et al (1996).…”
Section: Discussionmentioning
confidence: 99%
“…Polyploidy is widespread in the genus Brachiaria (Basappa et al, 1987;Honfi et al, 1990;Valle and Savidan, 1996;Bernini and Marin-Morales, 2001;Utsunomiya et al, 2005;Mendes-Bonato et al, 2002). An analysis of the DNA content of 435 accessions of 13 species of Brachiaria in the Brazilian collection, maintained at Embrapa Beef Cattle (Campo Grande, MS), revealed that only 13.04% are 2n whereas the others are polyploid, with a large predominance of tetraploids (58.13%) (Penteado et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the genus Brachiaria revealed that most species and accessions within the species are polyploid (Pritchard 1967;Nassar 1977;Ndikumana 1985;Basappa et al 1987;Valle and Savidan, 1996;Utsunomiya et al, 2005;Mendes-Bonato et al, 2002Pagliarini et al, 2008;Risso-Pascotto et al, 2003. Among the polyploid accessions there is evidence that some of them evolved from autopolyploidy (MendesBonato et al, 2002) and others from allopolyploidy (Mendes et al, 2006;Boldrini et al, 2009aBoldrini et al, ,b, 2010.…”
Section: Introductionmentioning
confidence: 98%